Artistic Symbiosis: Orson Welles’s Othello (1951) as Cinematic Opera - Fátima Chinita (Interfaces)
Early film theorist Ricciotto Canudo equated cinema with music because of the Seventh Art’s inherent plasticity; in the 21st century, plasticity extends to the soundtrack. In this article, I explore the fusion of cinema with the musical genre of opera. By considering that film is a performative medium, beyond the actors’ agency, I confirm music’s importance in it as part of the structure and style of opera. Unlike Franco Zeffirelli’s adaptation of Verdi’s opera Otello, Orson Welles’s adaptation of William Shakespeare’s play conforms to Jacques Aumont’s concept of “operatic film” in that it engenders a coexistence of the verbal and the non-verbal, balancing drama and music with a performative intention. However, this film is so musicalized and operatically rendered, especially through its soundtrack, that it exceeds Aumont’s intention and becomes what I call a “cinematic opera”: a film that is operatic in its artificial and ritualistic nature as well as in its well-woven soundtrack of music, sound effects and voice working together in a common musicalized pattern.